Different Types of Corona Discharges Associated With High‐Altitude Positive Narrow Bipolar Events Nearby Cloud Top. Issue 4 (14th February 2023) - Li, Dongshuai; Luque, Alejandro; Gordillo‐Vazquez, F. J.; Pérez‐Invernón, F. J.; Husbjerg, Lasse Skaaning; Neubert, Torsten; Chanrion, Olivier; Lu, Gaopeng; Zhang, Hongbo; Han, Jing; Lehtinen, Nikolai G.; Østgaard, Nikolai; et al.
Abstract: Single‐ and multi‐pulse blue corona discharges are frequently observed in thunderstorm clouds. Although we know they often correlate with Narrow Bipolar Events (NBEs) in Very Low Frequency/Low Frequency radio signals, their physics is not well understood. Here, we report a detailed analysis of different types of blue corona discharges observed by the Atmosphere‐Space Interactions Monitor during an overpass of a thundercloud cell nearby Malaysia. Both single‐ and multi‐pulse blue corona discharges were associated with positive NBEs at the top of the cloud, reaching about 18 km altitude. We find that the primary pulses of multi‐pulse discharges have weaker current moments than the single‐pulse discharges, suggesting that the multi‐pulse discharges either have shorter vertical channels or have weaker currents than the single‐pulse discharges. The subsequent pulse trains of the multi‐pulse discharges delayed some milliseconds are likely from horizontally oriented electrical discharges, but some NBEs, correlated with both single‐and multi‐pulse discharges, include small‐amplitude oscillations within a few microseconds inside their waveforms, which are unresolved in the optical observation and yet to be understood. Furthermore, by jointly analyzing the optical and radio observations, we estimate the photon free mean path at the cloud top to be ∼6 m. Plain Language Summary: Recent studies indicate that the blue corona discharges detected by the Atmosphere‐Space Interactions Monitor onboard the international space station have close association with a special type of intracloud discharges named Narrow Bipolar Events (NBEs). In this study, we present a detailed analysis of different types of NBE‐associated corona discharges detected by both optical and radio observations. All the detected corona discharges are found to be associated with unusual high‐altitude positive NBEs, which located a few kilometers below the cloud top where the cloud droplets have low impact on the optical observation. This allowed us to infer the physical properties of them and their parent thundercloud by using theoretical models. The results can provide important reference to further investigate the physical mechanism of corona discharge and their role in lightning initiations. Key Points: Corona discharges are found to be associated with unusual high‐altitude positive narrow bipolar events nearby cloud top Corona discharges are classified into different types according to their different optical and radio features The detailed features of corona discharges and their parent thundercloud are estimated using different theoretical models